STARKAP Protocol: preliminary assessment of safety and tolerability of dostarlimab in combination antiretroviral therapy (cART)-refractory HIV associated Kaposi’s Sarcoma - Claudia A. M. Fulgenzi; Alessia Dalla Pria; Alberto Giovanni Leone; Maria Martinez; Elena Ferrer Martinez Del Peral; Maria Eleanor Flores; Mark Bower; David J. Pinato (BMC Cancer)
Abstract Background Kaposi sarcoma (KS) is a mesenchymal malignancy induced by human herpes virus-8 (HHV-8). Whilst combined anti-retroviral therapy (cART) has substantially reduced the incidence of KS in people living with HIV (PLWH), KS remains the commonest neoplasia in this population. In up to 15–20% of cases, KS fails to respond to cART. T-cells immune exhaustion is thought to play a central role in mediating KS development and progression in PLWH receiving cART. The high reliance of PD-1 in shaping the cART-refractory phenotype poses a strong rationale for the use of PD-1 blocking antibodies against KS. Aims StarKap is a phase Ib, open label, single arm study aiming at evaluating the safety, tolerability of dostarlimab- an anti PD-1 antibody- in cART-refractory KS. Secondary endpoint is the evaluation of overall response rates by AIDS Clinical Trial Group (ACTG) criteria complemented by RECIST v1.1 in patients with visceral disease. Methods The trial will enrol 20 patients in total. After completion of the screening procedures, participants will receive the first dose of dostarlimab within 28 days. Dostarlimab will be administered at the dose of 500 mg evry 3 weeks for the first 5 cycles, and at 1000 mg every 6 weeks thereafter. Treatment will continue until disease progression, unacceptable toxicity, or completion of 1 year of treatment. The first 6 patients will be enrolled in a safety-lead-in phase, if no dose-limiting toxicities (DLTs) will occur within the 21 days in the first 6 participants, trial will continue. Patients will be monitored for the emergence of adverse events until 90 days after the last dose of treatment. Tumour response will be assessed as objective response rate (ORR) at cycle 4, cycle 8 and end of treatment. Tissue, bloods, and stool samples will be collected at baseline, on treatment and at end of treatment to satisfy the related translation plan.